Environmental ethics : from theory to practice - Hourdequin, Marion (London ; New York : Bloomsbury Academic, 2015)
"Environmental Ethics offers an up-to-date and balanced overview of environmental ethics, focusing on theory and practice. Written in clear and engaging prose, the book provides an historical perspective on the relationship between humans and nature and explores the limitations and possibilities of classical ethical theories in relation to the environment. In addition, the book discusses major theoretical approaches to environmental ethics and addresses contemporary environmental issues such as climate change and ecological restoration. Connections between theory and practice are highlighted throughout, showing how values guide environmental policies and practices, and conversely, how actions and institutions shape environmental values"--
Machine generated contents note: -- Part I: Environmental Values 1. Introduction: Bringing Values to Light 2. Classical Ethical Theories and the Environment 3. Anthropocentrism and its Critics: Broadening Moral Concern 4. The Social Roots of Environmental ProblemsPart II: Environmental Ethics in Practice 5. Ethics, Institutions and the Environment 6. Global Climate Change 7. Ecological Restoration 8. Engaging Environmental Concern, Promoting ChangeBibliographyIndex.
Includes bibliographical references and index.
Keywords: Environmental ethics; PHILOSOPHY / Ethics & Moral Philosophy; SCIENCE / Philosophy & Social Aspects; POLITICAL SCIENCE / Public Policy / Environmental Policy